Gene expression in farm poultry under the influence of T-2 toxin and the use of biological preparations - E. A. Yildirim; A. A. Grozina; L. A. Ilina; V. A. Filippova; G. Y. Laptev; E. S. Ponomareva; A. V. Dubrowin; K. A. Kalitkina; V. V. Molotkov; D. A. Akhmatchin; D. G. Tiurina (Acta Biomedica Scientifica, 2022)
Background. Feed-borne T-2 toxin may inhibit innate immune system function in birds.The aim. To evaluate the effect of T-2 toxin, artificially introduced with feed, on the expression level of a number of immunity-related genes in the tissues of the broiler digestive system.Materials and methods. The experiments were carried out in the vivarium of the FSC “VNITIP” RAS broilers of the Smena 8 cross from 33 to 47-day old. Experimental contamination of feed T-2 toxin was performed. The birds were divided into 4 groups of 5 animals each: I – control, receiving a diet without the introduction of T-2 toxin, II experimental – receiving a diet with the addition of T-2 toxin, III experimental – receiving a diet with the addition of T-2 toxin and the sorbent Zaslon2+, IV experimental – receiving a diet with the addition of T-2 toxin, the same sorbent Zaslon2+and Axtra Pro enzyme. The level of mRNA expression was analyzed by quantitative reverse transcription PCR.Results. The data obtained indicated the impact of T-2 toxin contamination of broiler feed on the modulation of the level of expression of genes associated with the functioning of the immune system in the cecum and pancreas. Exposure to T-2 toxin (group II) led to an increase in the expression of the pro-inflammatory gene IL-6 in the tissues of the caecum by 10.8 times and IL-8 in the pancreas by 3.89 times (p ≤ 0.05) compared with control group I. The effect of the sorbent, as well as the complex, including the sorbent and the enzyme, on the expression of broiler genes was positive. The sorbent without the enzyme showed greater efficiency than with the additional introduction of the enzyme.